THE INFLUENCE OF PRODUCT QUALITY AND LOCATION TOWARDS CUSTOMER SATISFACTION AT KOPI KENANGAN MANADO TOWN SQUARE - Monicha Natasya Magerite; Shinta J.C Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to know the influence of product quality and location towards customer satisfaction at Kopi Kenangan Manado Town Square. This study uses the quantitative method and using multiple linear regression test to determine the influence of product quality and location towards customer satisfaction. The sample for this study is 100 respondents. The sampling technique used is a purposive sampling method and the data collection method is in the form of a questionnaire that is run through Google Form. Testing and data analysis in this study using SPSS 26 software. The results shows that Product Quality (X1) partially have a positive and significant influence on Customer Satisfaction (Y). Location (X2) partially have a positive and significant influence on Customer Satisfaction (Y). Product Quality (X1) and Location (X2) simultaneously have a positive and significant influence on Customer Satisfaction (Y). Adjusted R Square value obtained from the results of the coefficient of determination (R2) of 0.648 explains that 64.8% of customer satisfaction can be explained by product quality and location. While the remaining 35.2% is explained by other variables not examined in this study.